Built‐in RNA‐mediated chaperone (chaperna) for antigen folding tailored to immunized hosts. Issue 7 (2nd May 2020) - Kim, Young‐Seok; Lim, Jongkwan; Sung, Jemin; Cheong, Yucheol; Lee, Eun‐Young; Kim, Jihoon; Oh, Hana; Kim, Yeon‐Sook; Cho, Nam‐Hyuk; Choi, Seongil; Kang, Sang‐Moo; Nam, Jae‐Hwan; et al.
Abstract: High‐quality antibody (Ab) production depends on the availability of immunologically relevant antigens. We present a potentially universal platform for generating soluble antigens from bacterial hosts, tailored to immunized animals for Ab production. A novel RNA‐dependent chaperone, in which the target antigen is genetically fused with an RNA‐interacting domain (RID) docking tag derived from the immunized host, promotes the solubility and robust folding of the target antigen. We selected the N‐terminal tRNA‐binding domain of lysyl‐tRNA synthetase (LysRS) as the RID for fusion with viral proteins and demonstrated the expression of the RID fusion proteins in their soluble and native conformations; immunization predominantly elicited Ab responses to the target antigen, whereas the "self" RID tag remained nonimmunogenic. Differential immunogenicity of the fusion proteins greatly enriched and simplified the screening of hybridoma clones of monoclonal antibodies (mAbs), enabling specific and sensitive serodiagnosis of MERS‐CoV infection. Moreover, mAbs against the consensus influenza hemagglutinin stalk domain enabled a novel assay for trivalent seasonal influenza vaccines. The Fc‐mediated effector function was demonstrated, which could be harnessed for the design of next‐generation "universal" influenza vaccines. The nonimmunogenic built‐in antigen folding module tailored to a repertoire of immunized animal hosts will drive immunochemical diagnostics, therapeutics, and designer vaccines. Abstract : We present a potentially universal platform for generating soluble antigens from bacterial hosts, tailored to immunized animals for Ab production. A novel RID docking tag derived from the immunized host, enhance the solubility and robust folding of the target antigen. Built‐in RNA‐mediated chaperone platform derived from the immunized host only elicited antibody responses to the target antigen and greatly enriched and simplified the screening of hybridoma clones of monoclonal antibodies (mAbs).